1989
DOI: 10.1037/0096-3445.118.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Repeated failure: A source of helplessness or a factor irrelevant to its emergence?

Abstract: We tested the validity of the egotism model of human helplessness. In contrast to the original theoretical approach of Seligman and his associates, which points to response-outcome noncontingency as the main source of helplessness, the egotism alternative proposes that repeated failure itself is the critical determinant of helplessness symptoms. Repeated failure threatens the self-esteem of the subject, who supposedly engages in a least-effort strategy during the test phase of a typical learned helplessness st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 22 publications
1
50
2
Order By: Relevance
“…In terms of general adaptive functions, cognitive exhaustion states seem especially disruptive to more complex problem solving requiring nonroutine, flexible steps of processing in either achievement or interpersonal domains. The primacy of the cognitive underpinnings of this phenomenon is supported by data showing that these deficits emerge in conditions which minimize the likelihood of effort withdrawal as an egoprotective maneuver, i.e., in the absence of social performance feedback, as well as in situations when negative mood is statistically controlled for (Kofta & Sedek, 1989;Sedek & Kofta, 1990). In another study, just after people had been exposed to uncontrollable events, their pattern of predecisional information search was altered in a way indicating cognitive exhaustion: Participants tended to avoid effortful information-gathering strategies (Sedek et al, 1993; for similar findings with dysphoric subjects, see Conway & Giannopoulos, 1993).…”
Section: Cognitive Exhaustion Modelmentioning
confidence: 65%
“…In terms of general adaptive functions, cognitive exhaustion states seem especially disruptive to more complex problem solving requiring nonroutine, flexible steps of processing in either achievement or interpersonal domains. The primacy of the cognitive underpinnings of this phenomenon is supported by data showing that these deficits emerge in conditions which minimize the likelihood of effort withdrawal as an egoprotective maneuver, i.e., in the absence of social performance feedback, as well as in situations when negative mood is statistically controlled for (Kofta & Sedek, 1989;Sedek & Kofta, 1990). In another study, just after people had been exposed to uncontrollable events, their pattern of predecisional information search was altered in a way indicating cognitive exhaustion: Participants tended to avoid effortful information-gathering strategies (Sedek et al, 1993; for similar findings with dysphoric subjects, see Conway & Giannopoulos, 1993).…”
Section: Cognitive Exhaustion Modelmentioning
confidence: 65%
“…Webster & Kruglanski, 1998)-the ability to achieve cognitive structure is not only determined by personal characteristics but also by situational factors. For example, factors such as priming, helplessness training, and level of expertise were found to affect ease or difficulty in using cognitive structuring (Baldwin, Carrell, & Lopez, 1990;Kofta & Sedek, 1989;VanLehn, 1989). In the present study we use informational helplessness training to operationalize AACS.…”
Section: Self-anchoring and Heuristic Information Processingmentioning
confidence: 96%
“…Studies support the notion that individuals can accumulate negative emotions over multiple failures. For example, Kofta and Sedek (1989) demonstrated that the negative emotions and feelings associated with repeated failures over time contributed to the emergence of learned helplessness (Seligman, 1975), suggesting that the impact of negative emotions was additive. Studies of grief associated with multiple losses in a relatively short period of time (childhood mourning [Kaufman and Kaufman, 2005], AIDS-related loss [Cherney and Verhey, 1996;Sikkema, Hansen, Kochman, Tate, and Difranceisco, 2004], and between spouses and parents [Bonanno, Moskowitz, Papa, and Folkman, 2005]) also demonstrate that the feelings and emotions generated by several losses are compounded and "accumulate" with each new loss.…”
Section: Frequency Of Project Failure and Accumulated Negative Emotionmentioning
confidence: 99%